Optimization Process for Esterification of Rubber Seed Oil (RSO) with Trimethylolpropane (TMP) - Salimon, Jumat; Ishak, Ainaatul Asmaa' (Journal of Science and Technology, 2022)
Trimethylolpropane (TMP) ester has the potential to serve as a basic material in the biolubricant production due to its biodegradability, environmental friendly and good thermal properties. Thus, an investigation on the optimization of esterification of TMP with rubber seed oil fatty acid was carried out with sulphuric acid acting as the catalyst. In seeking optimised reaction, various temperature levels, durations and catalyst concentrations were applied. The results show that RSO has successfully being converted to TMP ester with 78% of TE at the temperature of 150oC using 2% (w/w) of sulphuric acid at 5 hours reaction time. Purification of TMP ester resulted in percentage yield of 66.8% of TMP ester with a mixture of DE and TE at 0.9% and 99.1%, respectively. TMP ester was analysed using high temperature gas chromatography (GC-FID) to determine the percentage composition of ester formed and fourier transform infrared spectroscopy (FTIR) to confirm the structure.